If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5t + -4 = 4 + t Reorder the terms: -4 + 5t = 4 + t Solving -4 + 5t = 4 + t Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '-1t' to each side of the equation. -4 + 5t + -1t = 4 + t + -1t Combine like terms: 5t + -1t = 4t -4 + 4t = 4 + t + -1t Combine like terms: t + -1t = 0 -4 + 4t = 4 + 0 -4 + 4t = 4 Add '4' to each side of the equation. -4 + 4 + 4t = 4 + 4 Combine like terms: -4 + 4 = 0 0 + 4t = 4 + 4 4t = 4 + 4 Combine like terms: 4 + 4 = 8 4t = 8 Divide each side by '4'. t = 2 Simplifying t = 2
| 5(6x-10)=-20 | | (8a^2-6a-8)-(-6a^2+7a+5)= | | 4(n-6)-(2-3n)=6n | | 4x+1=34+7x | | (x-2)(x+6)=3x | | 3x+30=81 | | x^2+24x-112=0 | | -y=-x-4 | | b^2=2b | | t(t-7)=18 | | x^2-x+649=0 | | -2(x+5)+4x= | | -10-2x=x+5 | | y=x^2+3x-5 | | 10x-3x-9+3-x=18 | | 17x-8=12x+33 | | 4x-1=3x+4 | | 20t^2=64+64t | | 2x+7=4x+7 | | 4x^2-7x+13=6x+3 | | 5k-4k+6= | | 20t^2=64+64 | | 10+3y=-9 | | 6x^2-38x-80=0 | | -2c+12=2c-6+6c-12 | | -6x+8=14-3x | | b+b+b+6=6b+5-2b+9 | | y^2+7y-30=0 | | 4x-2=-2x-56 | | 7x-10=-37-2x | | 8k-6+3k-2k+3=4*33 | | 6-5x-2x=34 |